English Teacher’s Figurative Language in Classroom Teaching Process - Utami, Helaza Putri; Kholid, M. Ridho (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
This study aims to analyze the teachers' use of figurative language in their classrooms. Figurative language plays a crucial role in enhancing communication and fostering a conducive learning environment. The objectives of the research were to describe the kinds of figurative language on English Teachers' on teaching process in classroom at eight grade, the meaning of Figurative Language on English Teachers' on Teaching Process in Classroom at Eight grade at SMP N 3 Bandar Lampung. This research was descriptive qualitative research. The research design involved observational methods to capture and analyze instances of figurative language used by teachers. The subject of the research was the teacher and students at eight grade of SMP N 3 Bandar Lampung. Data was collected through direct observation and recording. The analysis found that from eight figurative languages in the classroom, only two types which included in the learning. They consisted of 2 similes and 15 metaphors. Therefore, irony, personification, hyperbole, allusion, metonymy, and symbol were not found in this research. The findings of this study contributed to understanding the impact of figurative language on classroom dynamics and student engagement, offering valuable implications for educational practices